Examining the Influence of Religious Awareness on the Level of Religious and Virtual Islamic Da’wah Content - M. Ahim Sulthan Nuruddaroini; Evi Fatimatur Rusydiyah; M. Yunus Abu Bakar (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The research aimed to examine how religious awareness affects the level of religiosity, with virtual Islamic da’wah content as an intervening variable. Data was collected from respondents using a survey method, and path analysis was used to test the relationship between these variables. The results indicate that religious awareness does not have a direct significant influence on the level of religiosity, with a path coefficient of 0.363. However, religious awareness does significantly influence the content of virtual Islamic da’wah, with a path coefficient of 0.012. Interestingly, the content of virtual Islamic da’wah itself does not significantly affect the level of religiosity, with a path coefficient of 0.880. The analysis of the coefficient of determination (R Square) revealed that the religious awareness model could only explain 1.5% of the variation in the level of religiosity, while the model for virtual Islamic da’wah content could only explain 1.2% of the variation in the da’wah content itself. Additionally, the results of the Sobell test show that virtual Islamic da’wah content is not an intervening variable that significantly mediates the influence of religious awareness on the level of religiosity. The conclusion drawn from this research is that there are likely other factors outside the model that have a greater influence on a person’s level of religiosity. These findings suggest the need for further studies to explore other factors that can influence an individual’s level of religiosity, as well as the role of virtual Islamic da’wah content in different contexts.